The psychological skills of volleyball players - Pan, T.; Li, G. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Most research regarding domestic and international studies on athletes` psychological skills were published based mainly on individual, rather than collective, studies of sport. This research investigates the psychological characteristics and gender differences of Chinese volleyball players, determining the impact of training duration and examining psychological characteristics of volleyball players of different ranks and court positions. Methods A total of 239 volleyball players from China (116 male and 123 female) from 22 volleyball teams were recruited for the survey. The teams came from 16 cities and they were participating in China`s Sixth City Games. The questionnaire of Psychological Skill Inventory for Sports (PSIS) by Mahoney was adopted for the study. The internal consistency coefficient in this study was .812, and the split-half reliability was .713. Results / Discussion There was no statistically significant difference between male and female players on six psychological skills. However, the psychological skill level of males was found to be slightly higher overall than that of females, which is consistent with earlier findings (Michael, 1992). Significant differences were found between first and second grade athletes. The results of this research show that there is no significant difference in the psychological skills of players of different court positions. In the factors of confidence and mental preparation, significant differences were found between players with 5 to 8 years of training in comparison to those with less than 3 years training. Conclusions The improvement of anxiety control, confidence, motivation and team focus should be more emphasized for female players in the training process. Volleyball players of a high level should improve their cognitive skills and maintain their psychological skills at a high level. Players with less than 3 years training should aim to improve their mental preparation and confidence. Players in the court positions of setter and freemen should improve skills of anxiety control, confidence and team focus.